2018
DOI: 10.4314/jasem.v22i8.27
|View full text |Cite
|
Sign up to set email alerts
|

Effect of priming agents on seed germination of three corn species

Abstract: This study determines the effect of different priming agents (water, sodium chloride, potassium nitrate and calcium sulphate) on seed germination and sprout development in Guinea corn (Sorghum bicolor), millet (Pennisetum glaucum) and popcorn maize (Zea mays var everta). Different concentrations of the priming agents (5, 10, 15 and 20 g/l) were used for a period of 24 hours and the primed seeds planted on Petri dishes at the same time. At the end of five days germination, effects of each of the priming agents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The study showed that both expired and non-expired pendimethalin were effective in decreasing weed growth and they all improved yield in Samnut 21, except that the treatments where pendimethalin expired were used had lower yield compared to the pendimethalin non-expired. Also, the treatment that showed the highest output was pendimethalin non-expired + one hand weeding at 6 WAS, this is an indication that integrated weed management is not only effective in weed suppression but enhances higher yield compared to other treatments.. (Amare et al, 2014;Olorunmaiye et al, 2014).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The study showed that both expired and non-expired pendimethalin were effective in decreasing weed growth and they all improved yield in Samnut 21, except that the treatments where pendimethalin expired were used had lower yield compared to the pendimethalin non-expired. Also, the treatment that showed the highest output was pendimethalin non-expired + one hand weeding at 6 WAS, this is an indication that integrated weed management is not only effective in weed suppression but enhances higher yield compared to other treatments.. (Amare et al, 2014;Olorunmaiye et al, 2014).…”
Section: Discussionmentioning
confidence: 91%
“…With the exception of the herbicide that reached its expiration date in 2011, the germination rate was continuously greater in the control treatment. (Olorunmaiye et al, 2014). As most of these farmers get rid of expired herbicides after harvest and then start to look for means to get another one when a new season comes around, the pertinent decision arises whether or not to use expired herbicides as weed control agent.…”
Section: Introductionmentioning
confidence: 99%